English Conversation Learning Model Needs Using Memory Palace Technique: English - Sufi Alawiyah (Prodi Tadris Bahasa Inggris, 2024)
This research aims to determine the need for an English conversation learning model using the Memory Palace technique. This qualitative research was conducted using a survey method. Data collection techniques use documents, observation, and questionnaires. The participants who were used as research objects were students in the 3rd and 4th semesters of 3 classes (n=100). Data analysis consists of three steps, namely data reduction, data presentation, and conclusion. The results of the research conclude that the components of the objectives needed are related to the demands for quality human resources in the global and learning era. The content components and sequence of teaching materials must be by current issues so that students' vocabulary becomes richer. In terms of teaching methods and approaches, the use of memory palaces is more appropriate for learning English conversation. Meanwhile, the learning evaluation component focuses on the concept of giving tests in groups and individually so that it is in line with achieving the required 6C competencies. These findings also have implications for the development of learning models that teachers must prepare before starting teaching activities.